MARKETPLACE GROWS INTEREST IN ENTREPRENEURSHIP OF UNDERGRADUATE MANAGEMENT STUDENTS, CLASS OF 2020 DEVELOPMENT UNIVERSITY PANCA BUDI MEDAN - Cindy Patrisia; Hendra Utama (RADJA PUBLIKA, 2024)
This research analysis aims to find out whether the marketplace fosters entrepreneurial interest in undergraduate management students class of 2020 at Panca Budi Development University, Medan. The data analysis technique used is an associative research method with the help of the SPSS program. This research uses simple linear regression analysis. The sample in this study was 96 respondents. Primary data collection uses a questionnaire. The research results show that Marketplace has a positive and significant effect on the entrepreneurial interest of 2020 Bachelor of Management students at Panca Budi Development University, Medan. Based on the results of the research and discussion as well as the conclusions that have been put forward, the author provides several suggestions which it is hoped can be used as input for students: Students must increase their knowledge of using market places comprehensively so that they see opportunities for entrepreneurship to develop skills such as creativity, problem solving, decision-making. risk, and entrepreneurship.